Interpolation of operators of weak type (ϕ_0, ψ_0, ϕ_1, ψ_1) in Lorentz spaces - Peleshenko, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We prove theorems of interpolation of quasilinear operators of weak type (φ0 , ψ0 , φ1 , ψ1 ) in the Lorentz spaces. The operators considered are the analogs of the Calderon and Benett operators for concave and convex functions φ0 (t), ψ0 (t), φ1 (t), ψ1 (t).